HUBUNGAN ANTARA DIMENSI BIG FIVE PERSONALITY DENGAN RIWAYAT KECELAKAAN SOPIR DI PERUSAHAAN X - Indiana Yanuar (Universitas Airlangga, 2016)
Data Global Status Report on Road Safety released by WHO in 2012 showed as many as 1.24 million people worldwide died from traffi c accidents. According to the Police Data Korlantas 2011–2013, Trucks ranks third as a vehicle that frequent accidents. Based on these conditions, do research on the truck driver in the company “X” Pasuruan. This study aims to determine the relationship between working time, rest time and the type of personality through the big fi ve personality theory with a history of occupational accidents suff ered by truckers in the company “X”. This was an analytical study with a cross-sectional approach. The subject of this study was the truck driver as many as 70 peopletaken by simple random sampling technique. This research was conducted in the town of Pasuruan in 2016. The data were analyzed by univariate and bivariate analysis. Results of this research, between working time and rest time with a history of occupational accidents were no relationship. Meanwhile there were relationship between the type of Conscientiousness in the big fi ve personality with a history of occupational accidents according to statistics chi-square test with sig 0.036. The driver who had a history of workplace accidents is dominated by a driver with that type has a characteristic is not intended or too much pursuit of the goal, lazy, inattentive, reckless, undisciplined, and likes to have fun. It can be considered companies in the recruitment process.Keywords: truck driver, big fi ve personality, occupational accidents